Evaluación de la función pulmonar en sobrevivientes COVID-19 dados de alta del Hospital Regional de Loreto, 2020-2021 - Zorrilla Videira, Josseline Alexandra (2025)
Objective: To evaluate pulmonary function in COVID-19 survivors discharged from the Regional Hospital of Loreto between April and June 2020 and followed for one year. Methodology: Analytical cross-sectional study within a longitudinal follow up of patients discharged after COVID-19. Results: A total of 57 patients were analyzed, 56.14% of whom were male; 45.61% had general comorbidities, and 28.07% had a history of pulmonary disease. Spirometry showed normal results in 68.42% of patients, while 31.58% had some type of functional alteration, mainly mild (15.79%), moderate (7.02%), and moderately severe (3.51%) restriction. The average age was 51.81 years, and the mean BMI was 28.94 kg/m². Average oxygen saturation was 96.89%, and the mean heart rate was 81.84 bpm. Most spirometric parameters followed a normal distribution, except for FET% and FIVC%, which required non-parametric tests. No statistically significant associations were found between pulmonary function patterns and clinical variables, but positive correlations were observed between oxygen saturation and FET% (r = 0.410) and FIVC% (r = 0.666). Conclusion: One year after hospital discharge, some patients still presented respiratory alterations, mainly of a restrictive pattern. Most recovered normal parameters, although some persistent sequelae were identified, highlighting the need for ongoing post-COVID follow-up.